A functional interplay between ZNF217 and Estrogen Receptor alpha exists in luminal breast cancers. Issue 8 (10th June 2014) - Nguyen, Nhan T.; Vendrell, Julie A.; Poulard, Coralie; Győrffy, Balázs; Goddard-Léon, Sophie; Bièche, Ivan; Corbo, Laura; Le Romancer, Muriel; Bachelot, Thomas; Treilleux, Isabelle; Cohen, Pascale A.
Abstract : We aimed at highlighting the role of ZNF217, a Krüppel‐like finger protein, in Estrogen Receptor‐α (ERα)‐positive (ER+) and luminal breast cancers. Here we report for the first time that ZNF217 and ERα proteins bind to each other in both breast cancer cells and breast tumour samples, via the ERα hinge domain and the ZNF217 C‐terminal domain. ZNF217 enhances the recruitment of ERα to its estrogen response elements (ERE) and the ERα‐dependent transcription of the GREB1 estrogen‐regulated gene. The prognostic power of ZNF217 mRNA expression levels is most discriminatory in breast cancers classified with a "good prognosis", particularly the Luminal‐A subclass. A new immunohistochemistry ZNF217 index, based on nuclear and cytoplasmic ZNF217 staining, also allowed the identification of intermediate/poor relapse‐free survivors in the Luminal‐A subgroup. ZNF217 confers tamoxifen resistance in ER+ breast cancer cells and is a predictor of relapse under endocrine therapy in patients with ER+ breast cancer. ZNF217 thus allows the re‐stratification of patients with ER+ breast cancers considered as cancers with good prognosis where no other biomarkers are currently available and widely used. Here we propose a model in ER+ breast cancer where ZNF217‐driven aggressiveness incorporates ZNF217 as a positive enhancer of ERα direct genomic activity and where ZNF217 possesses its highest discriminatory prognostic value. Highlights: ZNF217 and ERα proteins bind to each other in breast cancer cells. ZNF217 enhances the recruitment of ERα to its estrogen response elements. ZNF217 increases the ERα‐dependent transcription of estrogen‐regulated gene. ZNF217 is a predictor of relapse under endocrine therapy in ER+ breast cancers. ZNF217 allows the re‐stratification of patients with luminal A breast cancers.